Ultraviolet Irradiation‐Controlled Memory Effect in Graphene Field‐Effect Transistors. Issue 13 (11th February 2013) - Meng, Jie; Wu, Han‐Chun; Chen, Jing‐Jing; Lin, Fang; Bie, Ya‐Qing; Shvets, Igor V.; Yu, Da‐Peng; Liao, Zhi‐Min
Abstract : Control of graphene memory devices using photons, via control of the charge‐transfer process, is demonstrated by employing gate‐voltage pulses to program/erase the memory elements. The hysteresis in the conductance‐gate voltage‐dependence of graphene field‐effect transistors on a SiO2 substrate can be greatly enlarged by ultraviolet irradiation in both air and vacuum. An enhanced charge transfer between graphene and its surroundings, induced by ultraviolet illumination, is proposed.